O clero e as Cortes de 1361 - Hermínia Vasconcelos Vilar (Medievalista)
In 1361 D. Pedro gathered Cortes in Elvas, a very uncommon place if we take in account the places chosen for these meetings. One of things most remarkable of this Cortes was the presentation of a list of grievances by the Portuguese clergy to the king. List that was, several decades after, collected in the Ordenações Afonsinas.Normally seen as a reflection of the persistence of previous problems between clergy and kings, the content and context of these grievances deserve a more detailed analysis. In this article, we intend to draw attention to the implications of the frequent presentation of grievances by the clergy to the king or pope and also to the importance of the crisis of 1355 -1356 in the first years of governance of D. Pedro.